Autologous Platelet-Rich Fibrin in the Treatment of Refractory Macular Holes - Arif Koytak; Fadime Nuhoglu; Havvanur Bayraktar; Rukiye Ercan; Hakan Ozdemir (Case Reports in Ophthalmological Medicine, 2019)
Purpose. To describe a novel method for the treatment of refractory macular holes. Methods. Two case reports on the use of autologous platelet rich fibrin (PRF), followed by sulfur hexafluoride gas tamponade to facilitate closure of refractory macular holes. Results. Macular holes were succesfully closed within a week in both cases. Best corrected Snellen visual acuities improved from counting fingers to 0.16 in the first case, and from 0.05 to 0.2 in the second case. No complication occurred during or after the procedures. Conclusion. The use of autologous PRF seems to be a safe and effective alternative method for the treatment of refractory macular holes. Further experience and studies are required to assess the value of autologous PRF in the management of challenging macular hole cases of different etiologies. To the best of our knowledge, this is the first use of autologous PRF in the treatment of macular holes.